Ethnobotany of aromatic medicinal plants: preparations and uses of local flora in five rural communities located in the region of Baixo Tocantins, Pará, Brazil (Research, Society and Development, 2021)
Medicinal plants are a primary source of natural resources, used to treat conditions by the population of riverside communities located in the Brazilian Amazon. Thus, the objective was to carry out an ethnobotanical survey of the aromatic medicinal plants, as well as the indications, the parts of the most used plants, the ways of preparing home remedies and to verify the agreement values ​​for the main use of the species used by residents of five rural communities located in the Baixo Tocantins region, Pará, Brazil. The selection of employees took place through the “snowball” methodology. In this research 78 participants were interviewed in the age group from 35 to 82 years old, with a predominance of the female gender, and the plants with a predominance of use were lemongrass, tortoise and priprioca food. In total 29 species were collected and identified, included in 23 genera and 11 families, with Lamiaceae being the most representative. In these communities, aromatic medicinal plants, in addition to treating diseases, are part of culture, customs and strengthen social and coexistence relationships.